The Modification of Eco-Enzyme Liquid and The Effect on Tomato Preservation with Soaking Then Rinsing in Water Method - Yuliana, Meta (Universitas Pendidikan Mandalika, 2024)
Tomatoes are the popular fruit but having short shelf life. This fruit require some treatment to maintain it’s quality during post-harvesting. Eco-enzyme is a fermented liquid, it’s made by fermentation process of fresh waste vegetables or fruits. Previous study showed that spraying tomatoes with Eco-enzyme can maintain the shelf life of tomatoes. This study aim to observe the effect of various liquid in Eco-enzyme fermentation and it’s effect to tomatoes preservation by soaking method. The research was experiment research using quality scale of tomatoes. The Eco-enzyme was fermented using different liquid such as water, coconut water and rice rinsed water. Tomatoes were soaked with each Eco-enzyme treatment with 50% and 100% concentration of each liquid for 5 minutes then rinsed them and observed their quality for 8 days during storage process. The control treatments are non-soaked and non-rinsed tomatoes. The observation include the quality of tomatoes and the quality of Eco-enzyme. The result of this study found that modification of liquid in Eco-enzyme fermentation have different effect for tomatoes preservation. Soaking and rinsing method also have different effect for tomatoes. The best treatment for EE1 is EE1-rinse-concentration 50%, EE2 is EE2-rinse-concentration 100%, and EE3 is EE3-rinse-concentration 50%. The soaking followed rinsing was the best method for tomatoes preservation treatment using Eco-enzyme.